PDF Text Searching System - Ab. Ghani, Siti Aezane (Universiti Teknologi Petronas, 2006)
This project is to develop a text searching system that assist users to develop a simple PDFtext-searching system, whichis capable of searching and processing the information in text files on user PC and in local networks. The main purpose of developing this project is to assist users in finding PDF documents and files within their local drives, where the appropriate documents can be found by entering the desired search terms (keywords) in the PDF Text Searching System. There are two objectives that have been set for this project. The first objective is to perform a study and have a better understanding on the software that will be used in order to develop PDF text-searching system, and the second objective is to develop a PDF text-searching system, which is capable of searching and processing the information in text files on userPC and in local networks. For the methodology, Rapid Application Development (RAD) approach has beenemployed. The methodology has been chosenbecause it is effective and suitable for short duration project. It was designed for developer and user to join together and work intensively toward their goal. By using the RAD methodology, the project is able to be completed within the time allocated. In the results and discussion part, it covers all the outcome that obtains from the project completion, which is based on the surveys conducted and questionnaires. In this chapter, the findings that were gain will determine whether the proposed system is acceptable and meet with the user's needs. In order to provide better services, some suggestion being carried out for future enhancement. This can improve the current system to be more efficient and effective.